2012
DOI: 10.1088/0031-9155/57/4/1095
|View full text |Cite
|
Sign up to set email alerts
|

Single-heartbeat electromechanical wave imaging with optimal strain estimation using temporally unequispaced acquisition sequences

Abstract: Electromechanical Wave Imaging (EWI) is a non-invasive, ultrasound-based imaging method capable of mapping the electromechanical wave (EW) in vivo, i.e., the transient deformations occurring in response to the electrical activation of the heart. Achieving the optimal imaging frame rates, in terms of the elastographic signal-to-noise ratio, to capture the EW in a full-view of the heart poses a technical challenge due to the limitations of conventional imaging sequences, in which the frame rate is low and tied t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 42 publications
1
35
0
Order By: Relevance
“…The electromechanical activation has been imaged at typical frame rates of 800-2000 images/s using single diverging waves [35], [36]. Using 5 waves, we have shown in vivo in the human heart a strong improvement of both the B-mode and the velocity estimation quality compared to one diverging wave imaging.…”
Section: Discussionmentioning
confidence: 98%
“…The electromechanical activation has been imaged at typical frame rates of 800-2000 images/s using single diverging waves [35], [36]. Using 5 waves, we have shown in vivo in the human heart a strong improvement of both the B-mode and the velocity estimation quality compared to one diverging wave imaging.…”
Section: Discussionmentioning
confidence: 98%
“…The minimum frame rate needed to successfully recover cardiac strain has been studied by several groups (Langeland et al 2005; Chen et al 2009; Provost et al 2012). Chen et al (2009) conducted uniformly elastic tissue-mimicking (TM) phantom studies using a cyclic compression platform; their phantom experiment results obtained using a two-step one-dimensional (1D) cross-correlation method (Shi and Varghese 2007) showed that frame rates higher than 10 times the cyclic compression frequency was necessary to maintain high elastographic signal-to-noise ratio (SNR e ) levels (≈16dB) using radiofrequency (RF) signals.…”
Section: Introductionmentioning
confidence: 99%
“…However, they did not explore the impact of lower frame rates in their study (Langeland et al 2005). Recently, Provost et al (2012) proposed the use of a joint probability density function (pdf) map of the SNR e and strain probability distribution to analyze the frame rate problem for cardiac applications. They reported a sharp decline in the SNR e values in the joint pdf maps in the vicinity of 4% strain in their open-chest canine heart study using a phased array transducer operated at a 3.3 MHz center frequency (Provost et al 2012).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations